Dosimetric evaluation of nuclear interaction models in the Geant4 Monte Carlo simulation toolkit for carbon-ion radiotherapy - Kameoka, S.; Amako, K.; Iwai, G.; Murakami, K.; Sasaki, T.; Toshito, T.; Yamashita, T.; Aso, T.; Kimura, A.; Kanai, T.; Kanematsu, N.; Komori, M.; et al. (Radiological physics and technology, 2008)
We tested the ability of two separate nuclear reaction models, the binary cascade and JQMD (Jaeri version of Quantum Molecular Dynamics), to predict the dose distribution in carbon-ion radiotherapy. This was done by use of a realistic simulation of the experimental irradiation of a water target. Comparison with measurement shows that the binary cascade model does a good job reproducing the spread-out Bragg peak in depth-dose distributions in water irradiated with a 290 MeV/u (per nucleon) beam. However, it significantly overestimates the peak dose for a 400 MeV/u beam. JQMD underestimates the overall dose because of a tendency to break a nucleus into lower- Z fragments than does the binary cascade model. As far as shape of the dose distribution is concerned, JQMD shows fairly good agreement with measurement for both beam energies of 290 and 400 MeV/u, which favors JQMD over the binary cascade model for the calculation of the relative dose distribution in treatment planning.